An empirical examination of factors affecting consumer repurchase intention in department store’s online channel (post Covid-19) - Nugroho, Andrianto Prasetya; Etty Zuliawati Zed; Tri Mulyani Kartini (SEAN Institute, 2024)
This research aims to study factors affecting consumer repurchase intention in department store’s online channels. The study covers respondents from Jabodetabek area in Indonesia who have carried out transactions through the department store’s online channel and follow their social media. We chose the Matahari department store because it is the largest department store in Indonesia. Based on the theory of repurchase intention, we consider and identify the nexus between e-service quality, social media engagement, privacy concerns, and e-promotion. Data were collected from 100 samples. Multiple regression is used in this study's analysis to evaluate the hypothesis of each independent variable's effect on the dependent variable. The statistical program SPSS was utilized to help with the testing and analysis of the data gathered from survey responses. The findings show that e-service quality, social media engagement, privacy concerns, and e-promotion have a positive impact on repurchase intention